2019
DOI: 10.1177/1350650119873802
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three-lobed bearing shapes in floating-ring bearings on the nonlinear oscillations of high-speed rotors

Abstract: Floating-ring bearings are widely used in automotive turbocharger machinery because of their robustness, low cost and their suitability under extreme rotation speeds. This type of bearings, however, can become a source of noise due to oil whirl/whip instability. The stabilizing effect of lobed bearing shape is known in the literature, which encourages the researchers to substitute plain cylindrical full floating bearings with lobed geometries in their outer and inner clearances to prevent the rotor-bearing sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Soni and Vakharia [29,30] analyzed the static and dynamic characteristics of FRBs with elliptical two lobes using the finite element method, concluding that both were noticeably superior to circular FRBs. Zhang et al [31,32] also investigated this structure as well as FRBs with three lobes. Nonlinear simulation results demonstrated that the FRB with an elliptical ring and bushing could suppress sub-synchronous vibration, while the three-lobe FRB with a high preload factor could completely suppress it.…”
Section: Introductionmentioning
confidence: 99%
“…Soni and Vakharia [29,30] analyzed the static and dynamic characteristics of FRBs with elliptical two lobes using the finite element method, concluding that both were noticeably superior to circular FRBs. Zhang et al [31,32] also investigated this structure as well as FRBs with three lobes. Nonlinear simulation results demonstrated that the FRB with an elliptical ring and bushing could suppress sub-synchronous vibration, while the three-lobe FRB with a high preload factor could completely suppress it.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in a lobed bearing system, the bearing geometric center and centers of curvature of lobes do not coincide. 21,22 A study by Sharma and Kushare 23 investigated the effect of various roughness patterns on the performance of two-lobe bearing. It was reported that when the roughness pattern is considered in the longitudinal direction, the two-lobe journal bearing provides enhanced value of stability as compared to roughness patterns in other directions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. 8 examined numerically and experimentally the properties of the bearing with a multi-lobe fully floating ring bearing. They concluded that the use of multi-lobe FRBs leads to an important vibration reduction and a moderate increase in friction losses.…”
Section: Introductionmentioning
confidence: 99%